Association between the triglyceride-glucose index and the presence and severity of hemorrhoidal disease: a cross-sectional study based on retrospectively collected clinical data - Tingting Li; Li Jiang; Hanwen Yang; Jianan Li (Frontiers in Endocrinology, 2026)
Objective To investigate the association between the triglyceride-glucose (TyG) index and the prevalence and severity of hemorrhoidal disease in adults undergoing anorectal evaluation. Methods This cross-sectional study analyzed retrospectively collected data from 528 adults undergoing anorectal evaluation and fasting biochemical testing. The TyG index was calculated as ln[fasting triglycerides (mg/dL) × fasting plasma glucose (mg/dL)/2]. Multivariable logistic regression, restricted cubic spline analysis, subgroup, sensitivity, severity, and exploratory mediation analyses were performed to assess the association between TyG and hemorrhoidal disease. Results Among the 528 participants, 196 (37.1%) had hemorrhoidal disease. Its prevalence increased progressively across TyG quartiles, from 23.5% in Q1 to 53.8% in Q4 (P for trend<0.001). After adjustment for demographic, metabolic, lifestyle, medication-related, and bowel-related factors, each 1-unit increase in the TyG index was associated with higher odds of hemorrhoidal disease (OR = 1.68, 95% CI: 1.24–2.28; P = 0.001). Compared with Q1, participants in Q4 had significantly greater odds of hemorrhoidal disease (OR = 2.43, 95% CI: 1.34–4.41; P for trend=0.002). Restricted cubic spline analysis showed a significant overall association (P<0.001) without evidence of nonlinearity (P = 0.184). The findings remained consistent across subgroup and sensitivity analyses. A higher TyG index was also associated with advanced hemorrhoidal disease (OR per 1-unit increase=1.62, 95% CI: 1.01–2.61). Conclusion A higher TyG index was independently associated with hemorrhoidal disease severity. BMI partially mediated this association (~27%), suggesting a potential metabolic pathway that requires validation in longitudinal studies.